2021
DOI: 10.1021/acs.inorgchem.1c02094
|View full text |Cite
|
Sign up to set email alerts
|

A Dicobalt(II) Single-Molecule Magnet via a Well-Designed Dual-Capping Tetrazine Radical Ligand

Abstract: The recent years have witnessed the glory development for the construction of high-performance mononuclear single molecule magnets (SMMs) within a specific coordination geometry, which, however, is not well applied in cluster-based SMMs due to the synthetic challenges. Given that the monocobalt-(II) complexes within a trigonal-prismatic (TPR) coordination geometry have been classified as excellent SMMs with huge axial anisotropy (D ≈ −100 cm −1 ), here we designed and synthesized a new dual-capping tetrazine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…[58][59][60] The unsaturated and non-superimposed curves suggest the presence of significant magnetic anisotropy in these two compounds. [61][62][63][64] Obviously, the M versus H/kOe curve of 1 at 2.0 K shows a clear inflection at around 1.5 kOe, and reaches a maximum value of 4.69μ B at about 70 kOe. By comparison, the rapidly rising M curve can be detected in 1•CH 3 OH.…”
Section: Solvent Molecule Exchanges Of Compounds 1 and 1•ch 3 Ohmentioning
confidence: 99%
“…[58][59][60] The unsaturated and non-superimposed curves suggest the presence of significant magnetic anisotropy in these two compounds. [61][62][63][64] Obviously, the M versus H/kOe curve of 1 at 2.0 K shows a clear inflection at around 1.5 kOe, and reaches a maximum value of 4.69μ B at about 70 kOe. By comparison, the rapidly rising M curve can be detected in 1•CH 3 OH.…”
Section: Solvent Molecule Exchanges Of Compounds 1 and 1•ch 3 Ohmentioning
confidence: 99%
“…Therefore, it is widely used as a spin carrier in the design of molecular magnetic materials, 1,11,12 with the expected AF or ferromagnetic (FM) spin-exchange interaction. 13,14 In previous works, the primary strategy was to obtain higher spin organic magnetic materials based on molecular topology, 15,16 like π-conjugated rigid molecules, 17−19 metal ion coordination molecules, 20,21 and self-assembled molecules. 22−24 Since 1967, when Simmons and Fukunaga first proposed spiro conjugation, it has been confirmed by theoretical and experimental chemistry in many cases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nitronyl nitroxides are thermodynamically stable due to their electron-delocalized structure. Therefore, it is widely used as a spin carrier in the design of molecular magnetic materials, ,, with the expected AF or ferromagnetic (FM) spin-exchange interaction. , In previous works, the primary strategy was to obtain higher spin organic magnetic materials based on molecular topology, , like π-conjugated rigid molecules, metal ion coordination molecules, , and self-assembled molecules. …”
Section: Introductionmentioning
confidence: 99%
“…It is, however, still a great challenge to improve the magnetic behaviors of 4f-3d based SMMs. Recently, an appealing strategy is to use paramagnetic radical ligands for constructing 4f-3d based complexes, i. e. 2p-3d-4f system, [29][30][31][32][33][34][35][36][37][38] in which three kinds of different spins may work in a synergistic way resulting in interesting magnetic behavior. Andruh et al have reported a 2p-3d-4f SMM [Co II Dy III Rad] involving the end-off bicompartmental ligand combined with a nitronyl nitroxide unit.…”
Section: Introductionmentioning
confidence: 99%